The Effectiveness of Remote Patient Monitoring in Reducing the Risk of Rehospitalizations in COVID-19 Patients: A Meta-Analysis - Riadi, Dela; Trihandini, Indang; Sari, Dewi Nirmala; Wijaya, Fikri (Kesmas, 2025)
An integrated analysis of various Remote Patient Monitoring (RPM) studies is needed to evaluate the reduction rate of the risk of rehospitalization in COVID-19 patients. This meta-analysis aimed to provide an overview of the effectiveness of RPM. A literature search through online databases (PubMed, Science Direct, Scopus, ProQuest, and Embase) was conducted from 2019 to 2022. After using the Cochrane Collaboration's risk of bias tool, five studies on COVID-19 were selected. Based on the data collected from 2,685 participants (intervention = 1,060, control = 1,625), the use of RPM was found to reduce rehospitalization by 0.56 times compared to not using RPM (I2 = 9%; n = 2,685; OR 0.56 [95% CI 0.39-0.82]; p-value = 0.003). According to the characteristics analysis, sex, comorbidity of hypertension, heart failure, obesity, chronic lung, and chronic kidney disease had no significant effect on the risk being studied. It was only the comorbidity of diabetes that showed a significant impact. Both RPM intervention duration and long-term monitoring effectively reduced rehospitalization (>14 days). In brief, RPM may reduce hospitalizations in response to an impending epidemic. Future research should look into using RPM to treat chronic post-hospitalization conditions.